Mechanistic Insights into Cytosine-N3 Methylation by DNA Methyltransferase DNMT3A. Issue 17 (9th August 2019) - Dukatz, Michael; Requena, Cristina E.; Emperle, Max; Hajkova, Petra; Sarkies, Peter; Jeltsch, Albert
Abstract: Recently, it has been discovered that different DNA-(cytosine C5)-methyltransferases including DNMT3A generate low levels of 3mC [Rosic et al. (2018), Nat. Genet., 50, 452–459]. This reaction resulted in the co-evolution of DNMTs and ALKB2 DNA repair enzymes, but its mechanism remained elusive. Here, we investigated the catalytic mechanism of DNMT3A for cytosine N3 methylation. We generated several DNMT3A variants with mutated catalytic residues and measured their activities in 5mC and 3mC generation by liquid chromatography linked to tandem mass spectrometry. Our data suggest that the methylation of N3 instead of C5 is caused by an inverted binding of the flipped cytosine target base into the active-site pocket of the DNA methyltransferase, which is partially compatible with the arrangement of catalytic amino acid residues. Given that all DNA-(cytosine C5)-methyltransferases have a common catalytic mechanism, it is likely that other enzymes of this class generate 3mC following the same mechanism. Graphical Abstract: Unlabelled Image Highlights: DNA-(cytosine C5)-methyltransferases also generate low levels of 3mC. We studied the mechanism of 3mC generation by DNMT3A by mutating catalytic residues. Our data suggest that N3 methylation is caused by an inverted binding of C after base flipping.